INCOME SMOOTHING PADA INDUSTRI MANUFAKTUR - Sumarna, Alfonsa Dian (UP2M SEKOLAH TINGGI ILMU EKONOMI GALILEO, 2017)
This research uses panel data from manufacturing companies listed in Indonesian Stock Exchange (BEI) in the period from 2011 to 2015 to analyze the effect between cash holding, firm size, growth, dividend payout ratio, and leverage to income smoothing. The results indicate that there is a significant negative effect between cash holding and leverage to income smoothing, but there was no significant effect between firm size, growth and dividend payout ratio to income smoothing.